Successional changes in mycorrhizal type in the pioneer plant communities of a subalpine volcanic desert on Mt. Fuji, Japan - Fujiyoshi, Masaaki; Kagawa, Atsushi; Nakatsubo, Takayuki; Masuzawa, Takehiro (National Institute of Polar Research, 2005)
P(論文) Isolated island-like plant communities dominated by the perennial herb Polygonum cuspidatum are typical pioneer vegetation in the subalpine volcanic deserts of Japan. To study the relationship between mycorrhizal associations and plant community development, we conducted a survey of the mycorrhizal status of plants in subalpine island communities in a volcanic desert on Mt. Fuji. Roots of 45 native species, belonging to 23 families, were collected from island communities at 3 different successional stages: (I) pioneer communities dominated by P. cuspidatum, (II) mixed communities of herbs and grass, and (III) mixed communities of herbs and shrubs. Arbuscular mycorrhiza (AM) was the predominant mycorrhizal type in the early stages of community successions (I and II). P. cuspidatum, which had previously been reported as a non-mycorrhizal species, formed AM at the study site. In the later stage (III), 5 mycorrhizal types, AM, ecto-, ericoid, arbutoid and orchid mycorrhizal, were observed. Seven woody species had two types of mycorrhizas (AM and ectomycorrhiza). High spore densities of AM fungi were observed in the soil of the island communities, whereas few spores were observed in bare ground without vegetation cover. The average colonization levels of the AM fungi were within a wide range of 0.1 to 72%, independent of successional progress. These data show that marked increases in mycorrhizal types occur during the succession of island communities, although AM is the predominant mycorrhizal type throughout the successional process. departmental bulletin paper